Forage sorghum silage and summer annual silage and hays for growing steers and heifers - K. Bolsen; H. Ilg; M. Nuwanyakpa; Gerry L. Posler (Kansas Agricultural Experiment Station Research Reports, 1982)
Sorghum-Sudan hay and silage and sudangrass hay were compared with forage sorghum silage in an 80-day growing trial involving 60 calves. Calves fed forage sorghum gained 14% faster than those fed sudangrass hay (P<.05). Calves fed either of the two silages consumed less feed (P<.05) but were more efficient (P<.05) than those fed either of the two hays. This and two previous trials indicate that early-harvested summer annual silages and hays produce similar rates of gain but that silages are used 10 to 20% more efficiently by growing cattle. These forages have 75 to 90% of the relative feeding value of average-quality forage sorghum silage. With crude protein content of 12 to 15%, our summer annuals required little, if any, supplemental protein.
Keywords: Cattlemen& #x27; s Day; 1982; Report of progress (Kansas State University. Agricultural Experiment Station); 413; Beef; Sorghum silage; Hay; Steers; Heifers